PROGRAM CETAK SAWAH DAN KEBERLANJUTAN LINGKUNGAN: PERSEPSI MASYARAKAT DI TAHAP PRA DAN KONSTRUKSI DI KABUPATEN BOMBANA - Iskandar Zainuddin Rela; Dian Agustina (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2026)
The rice field cultivation program is one of the government's strategic policies in an effort to strengthen national food security through the expansion of agricultural land. In addition to being oriented towards increasing food production, the implementation of this program also has the potential to impact environmental sustainability and social conditions. This study aims to analyze community perceptions of the environmental impact of the implementation of the People's Rice Field Cultivation Program in Bombana Regency. The research was conducted in November 2025 using a survey method and a descriptive approach. The location was determined purposively, with the sample of respondents determined using simple random sampling. Data collection was carried out through observation, interviews, and documentation, then analyzed descriptively using a perception assessment scale. The results show that community perceptions of the implementation of the rice field cultivation program vary at each stage of the activity. In the pre-construction stage, particularly during the socialization activities, the community showed high and generally positive perceptions. Meanwhile, during the land acquisition and several construction stages, community perceptions were moderate, indicating concerns about potential environmental and social impacts. In general, the rice field cultivation program in Bombana Regency is perceived to provide economic and social benefits, but it still requires more planned environmental management and a participatory approach so that environmental sustainability and community acceptance can be optimally maintained.